2014
DOI: 10.1002/ijc.28856
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐sensing receptor silencing in colorectal cancer is associated with promoter hypermethylation and loss of acetylation on histone 3

Abstract: The calcium-sensing receptor (CaSR) is suggested to mediate the antiproliferative effects of calcium in colon. However, in colorectal cancer (CRC) the expression of the CaSR is silenced and the underlying mechanisms leading to its loss are poorly understood. We investigated whether loss of the CaSR expression in colorectal tumors is caused by DNA hypermethylation and imbalance of transcriptionally permissive/repressive histone alterations. We observed significantly lower CaSR mRNA expression (n = 65, p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…It is well established that the expression of the CaSR is reduced, or even lost during colorectal tumorigenesis . Recently, we demonstrated that changes in epigenetic patterns, like CaSR promoter 2 hypermethylation and loss of lysine 9 acetylation on histone 3, are among the mechanisms involved in silencing expression of the CaSR in colorectal tumors . However, our data suggested that other causes must also be involved in the loss of CaSR expression in these tumors.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…It is well established that the expression of the CaSR is reduced, or even lost during colorectal tumorigenesis . Recently, we demonstrated that changes in epigenetic patterns, like CaSR promoter 2 hypermethylation and loss of lysine 9 acetylation on histone 3, are among the mechanisms involved in silencing expression of the CaSR in colorectal tumors . However, our data suggested that other causes must also be involved in the loss of CaSR expression in these tumors.…”
mentioning
confidence: 56%
“…We conducted microarray analysis for microRNAs in Caco2/AQ and Caco2/15 cells, which are subclones derived from the Caco‐2 cell line to screen for potential microRNAs that might target the CaSR. Caco2/AQ and Caco2/15 cell lines were maintained under standard conditions for 21 days. These cells differentiate spontaneously in cell culture after reaching confluency .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations